2002
DOI: 10.1002/jmv.10128
|View full text |Cite
|
Sign up to set email alerts
|

Variant analysis and immunogenicity prediction of envelope gene of HCV strains from China

Abstract: The putative envelope protein E2 of hepatitis C virus (HCV) is the most variable antigenic fragment in the whole viral genome and is responsible mainly for the large inter- and intra-individual heterogeneity of the infecting virus. To analyze variation and immunogenicity of HCV envelope genes of HCV strains from China, the serum samples from 12 Chinese patients with chronic hepatitis C from 10 cities of China were amplified, sequenced directly, and compared with international strains reported previously. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…1). Although many reference sequences were included in the clusters, they were all of Chinese origin [14,17,[19][20][21][22]. Figure 1 provides an expanded view of cluster A and B (each is collapsed into a branch in the main tree) that were investigated previously and found to coincide with the ÔCultural RevolutionÕ in China [23].…”
Section: Analysis Of Subtype 1b Sequencesmentioning
confidence: 99%
“…1). Although many reference sequences were included in the clusters, they were all of Chinese origin [14,17,[19][20][21][22]. Figure 1 provides an expanded view of cluster A and B (each is collapsed into a branch in the main tree) that were investigated previously and found to coincide with the ÔCultural RevolutionÕ in China [23].…”
Section: Analysis Of Subtype 1b Sequencesmentioning
confidence: 99%
“…Phylogenetic tree based on E1 sequences of HCV subtype 1b isolates determined in this and other studies. Bold initials represent ten sequences reported by Cai et al [2002] (AH2: AF403231 isolated in Anhui province; SD2: AF403239 isolated in Shandong; SH2 and SH22: AF403234 and AF403237 isolated in Shanghai; ZJ2: AF403228 isolated in Zhejiang; HB2: AF403232 isolated in Hubei; BJ2: AF403236 isolated in Beijing; JX2: AF402571 isolated in Jiangxi; JS2: AF403239 isolated in Jiangsu; and SZ2: AF03238 isolated in Shenzhen). The eight accession numbers with geographic names in parenthesis indicate where these reference 1b sequences were isolated [Chen et al, 1992;Chou et al, 1993;Wang et al, 1993].…”
Section: Figmentioning
confidence: 99%
“…The eight accession numbers with geographic names in parenthesis indicate where these reference 1b sequences were isolated [Chen et al, 1992;Chou et al, 1993;Wang et al, 1993]. Isolate sh481 (this study) and AY194239 (Wuhan City) [Cai et al, 2002] of subtype 1a were used as outgroups. Percentages shown in italics represent bootstrap values and the bar at the base indicates the genetic distance per nucleotide site.…”
Section: Figmentioning
confidence: 99%
“…In a previous study [Zhang et al, 2003], four DHFR-HVR1 fusion proteins were expressed successfully in prokaryotic cells, these HVR1 sequences were selected based on the immunogenicity predicted by computer analysis [Cai et al, 2002] and the most reactive sequence (aa 384-410 ATYTTGGAASHNTRGFTSLFSSGSQQK) showed positive with 66.7% (20/30) sera of HCV infected patients. To improve the cross reactivity, a method for the reassembly of sequences from their random DNA fragments by DNA shuffling, resulting in vitro recombination is reported in this paper.…”
Section: Introductionmentioning
confidence: 99%